2015
DOI: 10.1063/1.4936277
|View full text |Cite
|
Sign up to set email alerts
|

Study of a contracted glow in low-frequency plasma-jet discharges operating with argon

Abstract: In this work, we present an experimental and theoretical study of a low frequency, atmospheric plasma-jet discharge in argon. The discharge has the characteristics of a contracted glow with a current channel of submillimeter diameter and a relatively high voltage cathode layer. In order to interpret the measurements, we consider the separate modeling of each region of the discharge: main channel and cathode layer, which must then be properly matched together. The main current channel was modeled, extending a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The derivation and details of the cathode layer model can be seen in Ref. 4, of which we here give a short account.…”
Section: A Model Of the Cathode Layermentioning
confidence: 99%
See 1 more Smart Citation
“…The derivation and details of the cathode layer model can be seen in Ref. 4, of which we here give a short account.…”
Section: A Model Of the Cathode Layermentioning
confidence: 99%
“…These latter aspects are particularly complex for gases other than noble gases, and especially in the case of air. We have recently presented a study of a low-frequency plasma jet (without a dielectric barrier) operating with argon 4 and found that a rather involved model is required to properly account for the plasma discharge characteristics. It was found that the discharge consists of a non-thermal plasma with a current channel of submillimeter diameter and that impact on the cathode by metastable excited argon atoms, generated under the action of the relatively high electric field in the cathode layer, are required to produce the flow of secondary electrons needed to sustain the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Among different kind of non-thermal atmospheric-pressure plasma sources, low-current (*0.1 A) plasma jets have rapidly gained importance in various plasma processing applications (including biomedical applications) because they can operate in open air providing plasmas without spatial confinement [5,[8][9][10][11]. An afterglow containing electrons, ions and relative long-lifetime radicals dragged from the confined discharge by a relatively large gas flow; is formed at the outflow of those sources.…”
Section: Introductionmentioning
confidence: 99%